Comparison of laboratory and field measurements of P and S wave velocities of a peridotite rock. (October 2016) - Vilhelm, J.; Ivankina, T.; Lokajíček, T.; Rudajev, V.
Abstract: In this study, surface seismic measurements in the field at a rock outcrop (peridotite) and laboratory high frequency seismic measurements of spherical rock samples were compared. Both the field and the laboratory velocities of P- and S- waves were determined using pulse-transmission technique. Special conditions at the field site enabled multi-directional measurement in three mutually orthogonal planes. The anisotropy of seismic P- and S- wave propagation was estimated. Special measurements using neutron diffraction were carried out making it possible to establish the influence of mineral crystallographic preferred orientations (CPOs) of bulk rock sample on elastic wave propagation and its anisotropy. It was determined that the deep peridotite rocks exhibit weak anisotropy. A good directional correspondence for different seismic waves (field/laboratory) even for 3D velocity calculated based on neutron diffraction was found. Highlights: We performed field and laboratory seismic measurement on peridotite rock. The anisotropy of seismic wave propagation was estimated and discussed. By means of neutron diffraction texture measurement we calculated anisotropy due to CPO. Anisotropy was determined by CPO while velocity values drop down due fracturing.